Can Trust Be Restored? Institutional Communication in Addressing Sexual Violence in Indonesian Higher Education - Vinda Maya Setianingrum; Pramana Pramana; Puspita Sari Sukardani; Rifqi Abdul Aziz (Jogjakarta Communication Conference (JCC), 2026)
Sexual violence in higher education has emerged as a critical issue that threatens the safety of academic communities and undermines public trust in educational institutions. In Indonesia, increasing reports of sexual violence on campuses have prompted regulatory responses and the establishment of institutional mechanisms for prevention and handling. However, the effectiveness of these mechanisms largely depends on how institutions manage communication in preventing, responding to, and addressing such cases. This study examines how institutional communication operates in addressing sexual violence within Indonesian higher education institutions and how it relates to the restoration of public trust. Using a qualitative multiple case study approach, this research investigates three Indonesian public universities that have implemented institutional frameworks for the prevention and handling of sexual violence. Data were collected through in-depth interviews with institutional actors, including members of prevention task forces, faculty, administrators, and students, as well as through document analysis. The findings reveal that institutional communication plays a pivotal role in shaping transparency, accountability, and responsiveness in handling sexual violence cases. Effective communication practices not only facilitate coordination among institutional actors but also contribute to rebuilding trust among campus communities and the broader public. The study highlights that communication governance within institutions is essential in addressing sexual violence as both a crisis and a structural issue. By demonstrating how communication practices influence institutional credibility, this research contributes to broader discussions on public trust, institutional accountability, and social impact in higher education governance.